Negative electrode for all-solid-state battery and all-solid-state battery comprising same

By forming an amorphous carbon layer of a porous sheet on the negative electrode current collector side of the all-solid state battery, the problems of lithium dendrites and negative electrode volume expansion are solved, and the life characteristics of the battery are significantly improved.

CN119497913APending Publication Date: 2025-02-21LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202480003247.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-19
Filing Date
2024-04-12
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

In all-solid state batteries, due to the growth of lithium dendrites and the volume expansion of the negative electrode, short circuits and capacity deterioration are easily caused, thereby shortening the battery life.

Method used

Amorphous carbon layer containing a porous sheet is formed on one side of the negative electrode current collector to suppress the formation of lithium dendrites, and volume expansion of amorphous carbon during buffering and discharge through the porous sheet.

Benefits of technology

Effectively inhibit the formation of lithium dendrites, reduce the volume expansion of the negative electrode, prevent cracking and crushing, and improve the life characteristics of all-solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119497913A_ABST
    Figure CN119497913A_ABST
Patent Text Reader

Abstract

The present invention relates to a negative electrode for an all-solid-state battery and an all-solid-state battery comprising the same, the negative electrode comprising: a negative electrode current collector; the amorphous carbon layer is positioned on one side of the negative electrode current collector; and a porous sheet inside the amorphous carbon layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims the benefit of and priority to Korean Patent Application No. 10-2023-0077975, filed on Jun. 19, 2023, the disclosure of which is incorporated herein by reference in its entirety.

[0002] The present invention relates to a negative electrode for an all-solid-state battery and an all-solid-state battery comprising the negative electrode. Background Art

[0003] Lithium secondary batteries, which are reusable and have high energy density, are attracting attention as new energy sources with environmentally friendly characteristics because they can significantly reduce the use of fossil fuels and do not generate byproducts in their use.

[0004] Lithium secondary batteries are gaining attention not only as energy sources for wearable or portable devices, but also as energy sources for high-power and high-energy-density devices such as electric vehicles. Therefore, research on lithium secondary batteries with high operating voltage and high energy density is becoming more active.

[0005] The lithium secondary battery is charged and discharged by the transfer of lithium ions between the positive electrode and the negative electrode, and a portion of the lithium ions that migrate to the negative electrode adhere to the surface of the negative electrode to form lithium nuclei, which may grow into lithium dendrites as dendrites.

[0006] When lithium dendrites formed and grown on the surface of the negative electrode come into contact with the positive electrode, they may cause a short circuit in the lithium secondary battery, which may shorten the life of the lithium secondary battery and is also a problem in ensuring reliable performance.

[0007] In addition, due to the weak strength of the solid electrolyte membrane placed between the positive and negative electrodes, high-energy-density all-solid-state batteries frequently short-circuit.

[0008] It is proposed to use lithium as a negative electrode active material to increase the energy density of an all-solid-state battery. Methods of using lithium as a negative electrode active material include using lithium or a lithium alloy as a negative electrode active material, or using lithium as an active material precipitated at the interface of a negative electrode current collector and a solid electrolyte by charging without forming any negative electrode active material layer on the negative electrode current collector.

[0009] When lithium is used as the negative electrode active material, lithium is precipitated on the negative electrode side during charging, and if the negative electrode active material layer is not formed, lithium is precipitated on the negative electrode current collector. When the all-solid-state battery is repeatedly charged and discharged, the lithium precipitated on the negative electrode side may grow into lithium dendrites through the gaps in the solid electrolyte. Such lithium dendrites may cause battery short circuit or capacity degradation. In addition, the volume expansion of the negative electrode during charging and discharging can cause stress in the negative electrode, resulting in cracking.

[0010] Therefore, a technology that can prevent lithium dendrite growth and solve the cracking problem is highly desired.

[0011] [Prior art literature]

[0012] [Patent Document]

[0013] Korean Patent Application Publication No. 10-2018-0091678 Summary of the invention

[0014] [Technical issues]

[0015] In order to solve the above problems, the inventors of the present invention conducted various studies and confirmed that forming an amorphous carbon layer containing a porous sheet on one side of the negative electrode current collector can inhibit the formation of lithium dendrites and minimize the volume expansion of the negative electrode caused by the charging and discharging of the all-solid-state battery, thereby completing the present invention.

[0016] Therefore, an object of the present invention is to provide a negative electrode for an all-solid-state battery, which can suppress the formation of lithium dendrites and minimize the volume expansion of the negative electrode, thereby preventing phenomena such as cracking and breakage from occurring in the negative electrode.

[0017] In addition, an object of the present invention is to provide an all-solid-state battery capable of improving the life characteristics of the all-solid-state battery by including the negative electrode for the all-solid-state battery.

[0018] [Technical solution]

[0019] In order to achieve the above object, the present invention provides a negative electrode for an all-solid-state battery, comprising:

[0020] Anode current collector;

[0021] an amorphous carbon layer located on one side of the negative electrode current collector; and

[0022] A porous sheet is inside the amorphous carbon layer.

[0023] The present invention also provides an all-solid-state battery, comprising: a positive electrode; a negative electrode; and a solid electrolyte layer disposed therebetween.

[0024] Wherein, the negative electrode is the negative electrode for the all-solid-state battery of the present invention,

[0025] Wherein, the solid electrolyte layer faces the amorphous carbon layer of the negative electrode.

[0026] [Beneficial Effects]

[0027] The negative electrode for an all-solid-state battery of the present invention can suppress the formation of lithium dendrites and minimize the volume expansion of the negative electrode, thereby preventing phenomena such as cracking and breaking from occurring in the negative electrode.

[0028] Therefore, an all-solid-state battery including the negative electrode can have improved lifespan characteristics. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The negative electrode for the all-solid-state battery of the present invention is shown.

[0030] Figure 2 An all-solid-state battery of the present invention is shown.

[0031] Figure 3 The all-solid-state battery of the present invention is shown in a charged state.

[0032] Figure 4 This is a graph showing the measured life characteristics of the all-solid-state battery of Experimental Example 1. DETAILED DESCRIPTION

[0033] Hereinafter, the present invention is described in more detail.

[0034] The terms and words used in this specification and claims should not be interpreted as their ordinary meanings or dictionary meanings, but should be interpreted as meanings and concepts consistent with the technical idea of ​​the present invention based on the principle that the inventor can define the concept of the term in the way he deems appropriate to best describe his invention.

[0035] The terms used in the present invention are only used to describe specific examples and are not intended to limit the present invention. Singular expressions include plural meanings unless the context clearly indicates otherwise. In the present invention, the terms "comprising" or "having" and the like are intended to specify the presence of the features, quantities, steps, actions, ingredients, parts or combinations thereof, and are not intended to exclude the presence or addition of more than one other features, quantities, steps, actions, ingredients, parts or combinations thereof.

[0036] Anode for all-solid-state batteries

[0037] The present invention relates to a negative electrode for an all-solid-state battery, wherein the negative electrode for an all-solid-state battery of the present invention may include: a negative electrode current collector;

[0038] an amorphous carbon layer located on one side of the negative electrode current collector; and

[0039] Porous sheet inside the amorphous carbon layer.

[0040] The negative electrode for the all-solid-state battery of the present invention does not include a negative electrode active material layer on the negative electrode current collector. In other words, the negative electrode of the present invention does not include any negative electrode active material and can be a negative electrode without a negative electrode.

[0041] Figure 1 The negative electrode (100) for the all-solid-state battery of the present invention is shown. Figure 1The negative electrode (100) for the all-solid-state battery of the present invention may be in the form of a negative electrode current collector (110) and an amorphous carbon layer (120) stacked on one side of the negative electrode current collector (110), wherein the porous sheet (130) is located inside the amorphous carbon layer (120). The porous sheet (130) may be in the form of a porous sheet buried in the amorphous carbon layer (120).

[0042] The negative electrode current collector (110) is not particularly limited as long as it has good conductivity and is electrochemically stable within the voltage range of the lithium secondary battery. For example, the negative electrode current collector (110) may be any metal selected from the group consisting of copper, aluminum, stainless steel, titanium, silver, palladium, nickel, alloys thereof, and combinations thereof, wherein the stainless steel may be surface-treated with carbon, nickel, titanium, or silver, wherein an aluminum-cadmium alloy is preferably used as the alloy, and calcined carbon, a non-conductive polymer whose surface is treated with a conductive material, or a conductive polymer may also be used.

[0043] The amorphous carbon layer (120) may be formed by dispersing amorphous carbon in a solvent to form a slurry and coating it on one side of the negative electrode current collector (110).

[0044] The amorphous carbon may include: carbon black, such as acetylene black, furnace black, or Ketjen black; or graphene.

[0045] The amorphous carbon layer (120) can be used to achieve the function of ion transfer. More specifically, the amorphous carbon layer (120) can enable lithium ions moving to the negative electrode (100) to transfer to the negative electrode current collector (110) without interfering with the movement of lithium ions from the positive electrode (200) to the negative electrode (100) or from the negative electrode (100) back to the positive electrode (200).

[0046] Therefore, when the negative electrode (100) for an all-solid-state battery is stacked with a solid electrolyte layer (300) and a positive electrode (200) to manufacture a battery and then charged, lithium ions that have migrated to the negative electrode (100) through the amorphous carbon layer (120) can be electrodeposited at the interface between the negative electrode current collector (110) and the amorphous carbon layer (120) to form a lithium layer (400), and the formation of lithium dendrites can be suppressed. Therefore, even if the negative electrode (100) for an all-solid-state battery of the present invention does not contain a negative electrode active material, lithium is electrodeposited at the interface between the negative electrode current collector (110) and the amorphous carbon layer (120) by charging, so that the function of the all-solid-state battery can be exerted, and the formation of lithium dendrites can be suppressed, thereby improving the life characteristics of the all-solid-state battery.

[0047] Since lithium ions are transported through amorphous carbon, the volume of amorphous carbon may expand during the charge and discharge process of the all-solid-state battery. This volume expansion may exert stress on the negative electrode (100), causing it to crack and deteriorate its stability, resulting in poor life characteristics of the all-solid-state battery.

[0048] Therefore, by including a support inside the amorphous carbon layer (120), the present invention attempts to buffer the volume expansion of amorphous carbon occurring during the charge and discharge process of the all-solid-state battery, thereby promoting the movement of lithium ions and improving the life characteristics of the all-solid-state battery by increasing its mechanical strength.

[0049] That is, the present invention may include a porous sheet (130) inside the amorphous carbon layer (120), wherein the porous sheet (130) functions as a support for the amorphous carbon.

[0050] The porous sheet (130) may be located inside (ie, buried in) the amorphous carbon layer (120) such that the pores and the surface of the porous sheet (130) contain amorphous carbon.

[0051] The porous sheet (130) may be in the form of a non-woven fabric, and may be made of polyethylene, polypropylene or a mixture thereof.

[0052] In addition, the porosity of the porous sheet (130) can be 70% to 95%. Within this porosity range, the porous sheet (130) can serve as a support for buffering the volume expansion of amorphous carbon that occurs during the charge and discharge process of the all-solid-state battery, thereby solving problems such as breakage or cracking of the negative electrode (100) for the all-solid-state battery.

[0053] The pores of the porous sheet (130) have an interconnected structure such that they penetrate from one side of the sheet to the other side, thereby allowing flowable materials to pass through.

[0054] The volume ratio of the porous sheet (130) to the amorphous carbon layer (120) can be 5:95 to 30:70, preferably 10:90 to 20:80. Within the above volume ratio range, the porous sheet (130) can act as a support for buffering the volume expansion of the amorphous carbon that occurs during the charge and discharge process of the all-solid-state battery. In addition, the amorphous carbon can promote the migration of lithium ions, inhibit the growth of lithium dendrites, and stably deposit lithium at the interface between the negative electrode current collector (110) and the amorphous carbon layer (120).

[0055] The negative electrode (100) for an all-solid-state battery can be manufactured by placing a porous sheet (130) on a negative electrode current collector (110), and then applying and drying a slurry containing amorphous carbon.

[0056] Alternatively, it may be manufactured by manufacturing a porous sheet (130) on a negative electrode current collector (110), and then coating and drying a slurry containing amorphous carbon.

[0057] In order to ensure the bonding force between the negative electrode collector (110) and the porous sheet (130), the porous sheet (130) can be placed or manufactured after casting a solution containing a binder on the negative electrode collector (110), and the binder can be any type of binder known in the art without limitation.

[0058] In addition, coating the slurry containing amorphous carbon on the porous sheet (130) can be such that the porous sheet (130) is located inside the amorphous carbon layer (120), and the amorphous carbon is located on the surface and in the pores of the porous sheet (130). In addition, the amorphous carbon can be located in a part of the pores, or the amorphous carbon can be arranged to block all the pores.

[0059] Preferably, a slurry containing amorphous carbon can be coated and dried on the porous sheet (130) so that the porous sheet (130) is located inside the amorphous carbon layer (120). As used herein, "inside" can mean that the porous sheet (130) is buried in the amorphous carbon layer (120). The porous sheet (130) has a structure of multiple interconnected pores, which are connected from one side of the sheet to the other side, so that the slurry containing amorphous carbon can be inserted into the pores, or the amorphous carbon can be inserted into the pores by rolling. Therefore, the pores can be filled with amorphous carbon, so that the surface of the negative electrode collector (110) can also have amorphous carbon.

[0060] The amorphous carbon layer (120) may further include a binder to ensure bonding between amorphous carbons and to ensure bonding between the negative electrode current collector (110) and the amorphous carbon layer (120).

[0061] The binder may include at least one selected from the group consisting of, for example, polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM rubber), styrene butadiene rubber, fluorinated rubber and copolymers thereof.

[0062] The amorphous carbon layer (120) may contain 1 to 10 wt %, preferably 3 to 7 wt % of a binder relative to the total weight of the amorphous carbon layer (120). In this case, the amorphous carbon layer (120) may mean that it does not contain an inner porous sheet (130), that is, it is composed only of amorphous carbon.

[0063] All-solid-state battery

[0064] The present invention also relates to an all-solid-state battery, which comprises: a positive electrode; a negative electrode; and a solid electrolyte layer arranged therebetween.

[0065] This negative electrode is the above-mentioned negative electrode for the all-solid-state battery of the present invention.

[0066] The solid electrolyte layer may face the amorphous carbon layer of the negative electrode.

[0067] Figure 2 The all-solid-state battery of the present invention is shown. Figure 2 The all-solid-state battery of the present invention is in the form of a negative electrode (100), a solid electrolyte layer (300) and a positive electrode (200) stacked in sequence, wherein the amorphous carbon layer (120) of the negative electrode (100) and the solid electrolyte layer (300) can face each other.

[0068] Figure 3 The charging state of the all-solid-state battery of the present invention is shown. Figure 3 It can be seen that a lithium layer (400) is formed at the interface between the negative electrode current collector (110) and the amorphous carbon layer (120). This may be because the lithium ions released from the positive electrode (200) migrate through the solid electrolyte layer (300) and the amorphous carbon layer (120) of the negative electrode (100), and are electrodeposited to form a lithium layer (400) at the interface between the negative electrode current collector (110) and the amorphous carbon layer (120).

[0069] Therefore, the all-solid-state battery of the present invention can be formed so that a lithium layer (400) is formed by charging at the interface between the negative electrode current collector (110) and the amorphous carbon layer (120). The lithium layer (400) may include both lithium metal formed in a layer and a porous structure (e.g., a structure in which lithium metal is agglomerated in the form of particles) in which lithium metal is not formed in a layer. Although the present invention is described with reference to the form of the lithium layer (400), it is obvious that this specification is not intended to exclude structures in which lithium metal is not formed in a layer.

[0070] The positive electrode ( 200 ) may include a positive electrode current collector and a positive electrode active material layer coated on one side or both sides of the positive electrode current collector.

[0071] The positive electrode current collector may be the same as the negative electrode current collector (110) described above.

[0072] The positive electrode active material layer may include a positive electrode active material and optionally a solid electrolyte, a conductive material, and a binder.

[0073] The positive electrode active material may be a lithium source for forming the lithium layer (400).

[0074] The positive electrode active material may vary depending on the type of all-solid-state battery. For example, the positive electrode active material may include, but is not limited to: layered compounds such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2), or compounds substituted with more than one transition metal; lithium manganese oxides such as Li 1+x Mn 2-xO4 (where 0≤x≤0.33), LiMnO3, LiMn2O3 or LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxide, such as LiV3O8, V2O5 or Cu2V2O7; LiNi 1-x M x O2 (wherein M is Co, Ni, Fe, Cr, Zn or Ta; and 0.01≤x≤0.1) represented by Ni-type lithium nickel oxide; represented by the formula LiMn 2-x M x A lithium manganese composite oxide represented by Li2Mn3MO8 (wherein M is Co, Ni, Fe, Cr, Zn or Ta; and 0.01≤x≤0.1); or Li2Mn3MO8 (wherein M is Fe, Co, Ni, Cu or Zn); x Mn 2-x Lithium manganese composite oxide with spinel structure represented by O4; LiCoPO4; LiFePO4; elemental sulfur (S8); or sulfur compounds such as Li2S n (where n is 1), organic sulfur compounds or carbon sulfur polymers ((C2S x ) n , wherein x is 2.5 to 50, and n is 2).

[0075] The conductive material is a material that electrically connects the electrolyte and the cathode active material and serves as a path for electrons to move from the current collector to the cathode active material, and may be used without limitation as long as it does not cause any chemical changes in the lithium secondary battery and has porosity and conductivity.

[0076] For example, the conductive material may be: porous carbon-based materials, such as carbon black, graphite, graphene, activated carbon or carbon fiber; metal fibers, such as metal mesh; metal powders, such as copper, silver, nickel or aluminum; or organic conductive materials, such as polyphenylene derivatives. These conductive materials may be used alone or in combination.

[0077] Products currently commercially available as conductive materials include acetylene black series (eg, Chevron Chemical Company or Gulf Oil Company), Ketjen Black EC series (Armak Company), Vulcan XC-72 (Cabot Company), and Super P (MMM). Examples include acetylene black, carbon black, and graphite.

[0078] In addition, the positive electrode (200) may further include a binder, wherein the binder further increases the binding force between the components constituting the positive electrode (200) and the binding force between them and the current collector, and any binder known in the art may be used.

[0079] For example, the adhesive can be one selected from the group consisting of: fluoroplastic adhesives, including polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE); rubber adhesives, including styrene butadiene rubber (SBR), acrylonitrile butadiene rubber and styrene isoprene rubber; cellulose adhesives, including carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose and regenerated cellulose; polyol adhesives; polyolefin adhesives, including polyethylene and polypropylene; polyimide adhesives; polyester adhesives; and silane adhesives.

[0080] The solid electrolyte may include at least one selected from the group consisting of a sulfide-based solid electrolyte, a polymer-based solid electrolyte, and an oxide-based solid electrolyte, and may preferably include a sulfide-based solid electrolyte.

[0081] The sulfide-based solid electrolyte may contain sulfur (S) and have ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and may include Li—PS-based glass or Li—PS-based glass ceramics.

[0082] Specifically, the sulfide-based solid electrolyte may include at least one selected from the group consisting of Li6PS5Cl, Li6PS5Br, Li6PS5I, Li2S-P2S5, Li2S-LiI-P2S5, Li2S-LiI-Li2O-P2S5, Li2S-LiBr-P2S5, Li2S-Li2O-P2S5, Li2S-Li3PO4-P2S5, Li2S-P2S5-P2S5, Li2S-P2S5-SiS2, Li2S-P2S5-SnS, Li2S-P2S5-Al2S3, Li2S-GeS2 and Li2S-GeS2-ZnS, preferably at least one selected from the group consisting of Li6PS5Cl, Li6PS5Br and Li6PS5I. Li6PS5Cl, Li6PS5Br and Li6PS5I may be argyrodite-type solid electrolytes. In addition, the sulfide-based solid electrolyte can be doped with trace elements, for example, Li6PS5Cl can be further doped with bromine (Br).

[0083] The polymer-based solid electrolyte is a composite of a lithium salt and a polymer resin, that is, a polymer electrolyte material formed by adding a polymer resin to a solvated lithium salt, and can exhibit a thermal conductivity of about 1×10 -7 S / cm or more, preferably about 1×10 -5 S / cm or above ionic conductivity.

[0084] Non-limiting examples of polymer resins may include at least one of the group consisting of polyether polymers, polycarbonate polymers, acrylate polymers, polysiloxane polymers, phosphazene polymers, polyethylene derivatives and oxyalkylene derivatives (e.g., polyethylene oxide), phosphate polymers, poly-stirred lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, polymers containing ion dissociative groups, etc. In addition, polymer electrolytes may include at least one of polymer resins such as branched copolymers obtained by copolymerizing, for example, a polyethylene oxide (PEO) main chain with an amorphous polymer (e.g., PMMA, polycarbonate, polysiloxane (PDMS) and / or phosphazene) as a comonomer, a comb polymer, and a cross-linked polymer resin.

[0085] In polymer solid electrolytes, lithium salts are + X - The anions of these lithium salts are not particularly limited, but may include F - , Cl - Br - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - or (CF3CF2SO2)2N - .

[0086] The oxide-based solid electrolyte may contain oxygen (O) and have an ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table. For example, it may include a metal selected from the group consisting of LLTO-based compounds, Li6La2CaTa2O 12 、Li6La2ANb2O 12 (where A is Ca or Sr), Li2Nd3TeSbO 12 、Li3BO 2.5 N 0.5 , Li9SiAlO8, LAGP compounds, LATP compounds, Li1 + x Ti 2-x Al x Si y (PO4) 3-y (where 0≤x≤1 and 0≤y≤1), LiAl x Zr 2-x (PO4)3 (where 0≤x≤1), LiTi x Zr 2-x At least one of the group consisting of (PO4)3 (wherein 0≤x≤1), LISICON compounds, LIPON compounds, perovskite compounds, Nasicon compounds and LLZO compounds.

[0087] The solid electrolyte layer (300) may include a solid electrolyte having lithium ion conductivity, and may include any of the above-mentioned solid electrolytes. It may also include a binder, wherein the binder is as described above.

[0088] The present invention has no particular limitation on the preparation of the all-solid-state battery, and known methods may be used.

[0089] For example, a solid electrolyte membrane is disposed between a positive electrode (200) and a negative electrode (100), and then a battery cell is assembled by compression molding or calendering. The assembled battery cell is then mounted in an external material and sealed by hot pressing. As the external material, a laminated package of aluminum or stainless steel and a metal container such as a cylindrical or prismatic container can be used.

[0090] In one example, the positive electrode (200) is prepared by a slurry coating process in which a slurry composition including an electrode active material, a solvent, and a binder is prepared, coated, and then dried to prepare the electrode.

[0091] The method of applying the positive electrode slurry to the current collector may include distributing the positive electrode slurry onto the current collector and uniformly dispersing the positive electrode slurry using a scraper, die casting, comma coating or screen printing. In addition, the positive electrode slurry can be formed on a separate substrate and then bonded to the current collector by pressing or laminating. In this case, the final coating thickness can be controlled by adjusting the concentration of the slurry solution or the number of coatings.

[0092] The drying process is a process for removing solvent and moisture from the slurry to dry the slurry coated on the metal current collector, and the drying process may vary depending on the solvent used. For example, the drying process is carried out in a vacuum oven at 50°C to 200°C. Drying methods include, for example, drying by warm air, hot air or low humidity air, vacuum drying or irradiation with (far) infrared or electromagnetic radiation. The drying time is not particularly limited, but is generally 30 seconds to 24 hours.

[0093] After the drying process, the method may further include a cooling process, wherein the cooling process may be a slow cooling to room temperature to ensure that the recrystallized structure of the binder is well formed.

[0094] The shape of the all-solid-state battery is not particularly limited and may be cylindrical, laminated, coin-shaped, or the like.

[0095] Example

[0096] Hereinafter, preferred examples of the present invention are described in order to illustrate the present invention, but it is obvious to those skilled in the art that various changes and modifications may be made within the scope and technical concept of the present invention, and these changes and modifications fall within the scope of the appended claims.

[0097] <Preparation of all-solid-state batteries>

[0098] Example 1

[0099] The positive electrode active material (NCM811), conductive material (carbon fiber), solid electrolyte (Li6PS5Cl) and binder (polytetrafluoroethylene) were mixed in a weight ratio of 84:0.2:14.8:1, and the mixture was applied to the positive electrode collector, dried and calendered to prepare the positive electrode.

[0100] The solid electrolyte (Li6PS5Cl) and the binder (styrene-butadiene-styrene copolymer) were mixed in a weight ratio of 98:2, and the mixture was added to anisole to form a slurry. The slurry was coated on a release film (polyethylene terephthalate) using a bar coater and dried, and the release film was removed to prepare a solid electrolyte layer.

[0101] SUS with a thickness of 10 μm was prepared as the negative electrode current collector. A solution containing a binder (PVDF) was cast on the negative electrode current collector, and a porous sheet (PP / PE non-woven fabric, porosity 89%) was placed on it. A slurry of acetylene black and a binder (PVDF) with a weight ratio of 93.5:6.5 was applied and dried to prepare an amorphous carbon layer. The negative electrode comprises an amorphous carbon layer on the negative electrode current collector and a porous sheet inside the amorphous carbon layer.

[0102] The all-solid-state battery is prepared by sequentially stacking a positive electrode, a solid electrolyte layer, and a negative electrode with the solid electrolyte layer and the amorphous carbon layer of the negative electrode facing each other.

[0103] Comparative Example 1

[0104] SUS with a thickness of 10 μm was prepared as a negative electrode current collector. An amorphous carbon layer was prepared by coating a slurry of acetylene black and a binder (PVDF) in a weight ratio of 93.5:6.5 and drying. The negative electrode had an amorphous carbon layer on the negative electrode current collector and did not contain a porous sheet inside the amorphous carbon layer.

[0105] A positive electrode and a solid electrolyte layer were prepared in the same manner as in Example 1, thereby preparing an all-solid-state battery.

[0106] Experimental Example 1. Measurement of Life Characteristics of All-Solid-State Batteries

[0107] The life characteristics of the all-solid-state batteries of Example 1 and Comparative Example 1 were measured.

[0108] The life characteristics are measured as the capacity retention rate of the all-solid-state battery after 50 charge and discharge cycles, in which the charge is performed at 0.33C to 4.25V, 0.1C cutoff, and the discharge is performed at 0.33C to 3.0V in CC mode at a temperature of 60°C.

[0109] The results are Figure 4 Shown in.

[0110] The all-solid-state battery of Example 1 of the present invention showed a capacity retention rate of 92.6%.

[0111] However, the all-solid-state battery in Comparative Example 1 short-circuited at the 16th cycle and showed very poor life characteristics.

[0112] In other words, it can be seen that in the negative electrode for all-solid-state batteries, the inclusion of a porous sheet inside the amorphous carbon layer not only inhibits the formation of lithium dendrites, but also buffers the volume expansion of amorphous carbon that occurs during charging and discharging of the all-solid-state battery, thereby promoting the movement of lithium ions and solving the problem of damage to the negative electrode, thereby providing an all-solid-state battery with excellent life characteristics.

[0113] [reference numerals]

[0114] 100: Negative electrode

[0115] 110: Negative electrode current collector

[0116] 120: Amorphous carbon layer

[0117] 130: porous sheet

[0118] 200: Positive

[0119] 300: Solid electrolyte layer

[0120] 400: Lithium layer

Claims

1. A negative electrode for an all-solid-state battery, comprising: Anode current collector; an amorphous carbon layer located on one side of the negative electrode current collector; and A porous sheet is provided within the amorphous carbon layer. 2 . The negative electrode for an all-solid-state battery according to claim 1 , comprising amorphous carbon in the pores and on the surface of the porous sheet.

3. The negative electrode for an all-solid-state battery according to claim 1, wherein: The porous sheet is a nonwoven fabric.

4. The negative electrode for an all-solid-state battery according to claim 3, wherein: The nonwoven fabric is made of polyethylene, polypropylene or a mixture thereof.

5. The negative electrode for an all-solid-state battery according to claim 1, wherein: The porosity of the porous sheet is 70% to 95%.

6. The negative electrode for an all-solid-state battery according to claim 1, wherein: The volume ratio of the porous sheet to the amorphous carbon layer is 5:95 to 30:

70.

7. The negative electrode for an all-solid-state battery according to claim 1, wherein: The amorphous carbon layer further includes a binder.

8. The negative electrode for an all-solid-state battery according to claim 7, wherein: The amorphous carbon layer includes 1 wt % to 10 wt % of a binder based on a total weight of the amorphous carbon layer.

9. The negative electrode for an all-solid-state battery according to claim 1, wherein: No negative electrode active material layer is formed on the negative electrode current collector.

10. An all-solid-state battery comprising: a positive electrode; a negative electrode; and a solid electrolyte layer disposed therebetween, in, The negative electrode is the negative electrode for the all-solid-state battery according to claim 1, Wherein, the solid electrolyte layer faces the amorphous carbon layer of the negative electrode.

11. The all-solid-state battery according to claim 10, wherein: When the all-solid-state battery is charged, lithium is electrodeposited at the interface between the negative electrode current collector and the amorphous carbon layer.

Citation Information

Patent Citations

  • Anode for all solid state secondary battery, all solid state secondary battery and method of manufacturing the same

    KR1020180091678A

  • Method for providing safe counseling service of academies through anonymization of counselors

    KR1020230077975A